The derivation ability of verbs that denote parakinesic processes - Папідзе, Надія Вікторівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article describes the structure of word-building paradigms of verbs that describe parakinesic processes. The allocation of verbs in a separate lexical-semantic group, which is a peripheral component of macrofield of motion has been offered. Aktants and syrkonstants matrix of analyzed verbs have been established, valence opportunities have been defined. Among the derivatives of the first degree of derivation three blocks have been singled out: substantival, adjectival and verbal. The process of semantic and word building transformations in a pair «offormative – derivative» has been traced. Within the different types of word building blocks derivational meanings, realized by derivatives, and instruments of their expression have been found.